Familial factors, depression and cognitive decline: A longitudinal mediation analysis based on latent growth modeling (LGM) - Haoran Wang; Chunyan Yang; Ye Yao (International Journal of Methods in Psychiatric Research, 2022)
Abstract Background Cognitive decline of ageing population has become one of the major public health challenges worldwide, and familial factors (such as household income, marital status, etc.) have been identified as risk factors. Currently, we mainly focused on two familial factors: living with spouse/child and intergenerational rearing (taking care of grandchildren), exploring their relations with cognitive ageing. We also tested the possible mediating role of depression between the two family factors and cognitive decline. Methods Data was derived from China Health and Retirement Longitudinal Study (CHARLS) database, and a total of 8474 participants (3602 females, mean age = 69.64) were included in the current research. Latent growth model (LGM) has been constructed for cognitive functions, with initial level and declining rate being estimated respectively. We further examined: (1) whether living with spouse/child and intergenerational rearing could influence the declining trajectory (initial level and declining rate) of elders’ cognitive functioning; (2) and if so, whether depression could mediate the effects of living with spouse/child and intergenerational rearing on cognitive functioning. Results First, while living with spouse/child was related to higher initial level of cognitive functions and slower declining rate, intergenerational rearing was associated with neither of them. Second, growth trajectory of depression partly mediated the effects of living with spouse/child on cognitive functioning (Indirect effect = 0.14; p < 0.01). Conclusions Familial factors (living with spouse/child and intergenerational rearing) may be influential on declining trajectories of elders’ cognitive functions, and depression may mediate such effects. More research efforts are needed to investigate the mechanisms underlying the relations between familial factors and cognitive ageing.